APLIKASI KOMPOS YANG DIPERKAYA DENGAN BERBAGAI BAHAN UNTUK TANAMAN KEDELAI (Glycine max L. Merril) DIANTARA TANAMAN SAWIT MUDA DI LAHAN GAMBUT - Riadi, Munal; ', Nelvia; ', Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The total area of oil palm plantations in Indonesia about 7 million in Riau which is about 3 million ha. Land has not been optimally covered by oil palm crop of young (aged approtimately three years), so that they can be planted with soybean as intercrops in oil palm plantation . The research was conducted in the village of Kualu Nenas, District of Kampar, Riau Province. The research aims to study to the effeet of the application of mixture of compost of oil palm empty fruit bunches, boiler ash, liquid waste of palm oil mill and trichoderma  growth and yields of soybean  in oil palm plantations on peatland. The study was conducted through an experimen using randomized block dising (RBD), which consists of 8 treatment A : Without treatment, B : 5 tons of compost of OPEFB/ha, C : 5 tons of compost of OPEFB + 0.5 tons of boiler ash/ha, D : 5 tons of compost of OPEFB + 1 boiler ash/ha, E : 5 tons of compost of OPEFB + 1,5 boiler ash/ha, F : 5 tons of compost of OPEFB + 0.5 tons of boiler ash + 10 kg trichoderma + 30 L liquid waste of palm oil mill/ha, G : 5 tons of compost of OPEFB + 1 ton boiler ash + 10 kg trichoderma + 30 L liquid waste of palm oil mill/ha, H : 5 tons of compost of OPEFB + 1.5 tons boiler ash + 10 kg trichoderma + 30 L liquid waste of palm oil mill/ha, each repeated three times. The parameters observed were plant height, number of primary branches number of pods, pod percentage pithy. The results showed that treatment G : 5 tons of compost of OPEFB + 1 ton boiler ash + 10 kg trichoderma + 30 L liquid waste of palm oil mill/ha, increased plant height and number of pods significantly compared with without treatment, but not significantly different to the parameter number of primary branches, days to flowering and pod percentage pithy. Keywords : Soybean, Peatland, Compost of Epaty Bunch of Oil Palm, Boiler Ash, Trichoderma  and Liquid Waste of palm oil mill.